2018
DOI: 10.4103/ijem.ijem_148_17
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a patient education module on diabetic foot care in outpatient setting: An open-label randomized controlled study

Abstract: Background:A large number of patients with diabetes mellitus are unaware of foot care and are at risk of developing foot ulcer and amputation. This increases healthcare burden due to preventable complication of diabetes.Aims:We conducted this study to assess the effectiveness of a foot care education module for diabetes developed by us.Materials and Methods:One hundred and twenty-seven patients with diabetes mellitus attending our outpatient were randomized into intervention (n = 63) and control groups (n = 64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 19 publications
(20 reference statements)
0
18
0
4
Order By: Relevance
“…One limitation of this study is the relatively short follow-up period. Although other studies reevaluated patients after 6 months or 1 year, in this study the investigators reevaluated participants after 1 month, the same follow-up period used in the study by Rahaman et al 29 Extending this time period would help determine the curve of forgetting after the training session.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One limitation of this study is the relatively short follow-up period. Although other studies reevaluated patients after 6 months or 1 year, in this study the investigators reevaluated participants after 1 month, the same follow-up period used in the study by Rahaman et al 29 Extending this time period would help determine the curve of forgetting after the training session.…”
Section: Discussionmentioning
confidence: 99%
“…25 The education method appears to play a role in the effectiveness of the intervention. Numerous studies [19][20][21][26][27][28] have shown that with therapeutic education either by written or audiovisual means, 22,29 or through practical or theoretical interventions, 30 the levels of knowledge and self-care of patients with DM increase. In contrast, other types of interventions have not improved self-care outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Other forms of education can be online. This form of education can be accessed anytime and by any family member, which provides consistency and spread of knowledge about foot care [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, although the survey participants had a little safe drug use education experience, they reported high satisfaction with that education and indicated that they prefer education in the form of on-site lectures and audio-visual materials rather than other methods such as textbooks. Some studies also found that education using audio-visual methods is more effective than that using brochures or pamphlets [49][50][51]. Therefore, these preferred types of educational materials need to be developed and adapted to help ensure the safety of these individuals.…”
Section: Discussionmentioning
confidence: 99%